2009
DOI: 10.1167/iovs.08-2606
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β–Induced Disruption of Barrier Function in Cultured Human Corneal Epithelial Cells

Abstract: IL-1beta induced the redistribution of ZO-1 and occludin from TJs of HCE cells and thereby disrupted the barrier function of these cells in a manner dependent on NF-kappaB. These effects of IL-1beta may contribute to the loss of corneal epithelial barrier function associated with ocular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 59 publications
5
45
0
Order By: Relevance
“…TNF-a was found to disrupt the epithelial cell tight junctions, by affecting the localization of ZO-I at tight junctions (28). Similarly, IL-I Pcan induce the redistribution of ZO-I, thereby contributing to the reduced barrier function of the corneal epithelium (29). Our data suggest that the MPS-induced IL-I P and TNF-a production may lead to epithelial barrier dysfunction in the corneal epithelium, as found in our cytotoxicity data.…”
Section: Cytokine Protein Contents In Hce Cells Following Mpss (50%supporting
confidence: 77%
“…TNF-a was found to disrupt the epithelial cell tight junctions, by affecting the localization of ZO-I at tight junctions (28). Similarly, IL-I Pcan induce the redistribution of ZO-I, thereby contributing to the reduced barrier function of the corneal epithelium (29). Our data suggest that the MPS-induced IL-I P and TNF-a production may lead to epithelial barrier dysfunction in the corneal epithelium, as found in our cytotoxicity data.…”
Section: Cytokine Protein Contents In Hce Cells Following Mpss (50%supporting
confidence: 77%
“…Previous studies have similarly found increased mRNA expression of IL-1␤ in alveolar and monocyte-derived macrophages, but not primary human bronchial epithelial cells, following lung injury or influenza virus infection (14,16,41). IL-1␤, a cytokine involved in inflammatory responses, cell growth, and tissue repair, is frequently associated with ocular disease processes (10,20,26,27,43). Similar to our findings, a previous study found that RSV infection of corneal epithelial cells resulted in an upregulation of secreted IL-1␤ cytokine without a substantial change in cellular IL-1␤ mRNA levels (10).…”
Section: Discussionmentioning
confidence: 94%
“…IL-1␤ has known roles in ocular pathology and inflammation in ocular cells and has previously been shown to disrupt the barrier function of human corneal epithelial cells in an NF-B-dependent manner (27). The detection of elevated levels of IL-1␤ following NL/219 virus infection in human ocular but not respiratory cells prompted us to examine the induction of NF-B activation in both cell types to explore both tissue-specific and subtype-specific responses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACTH 4-10 synthetic improves the paracellular pathway via inhibition mechanism activation NFkB through ERK1/2 and p38 signalling pathways 31 . After that, the decreased expression of TNFα and IL-1β will cause the decreased induction redistribution of ZO-1, Ocludin and lower TER>80% approximately 32,33 . Another mechanism relates to the ability of ACTH [4][5][6][7][8][9][10] to reduce the increased NO, oxidants that have the ability to impair BBB functions 34 through the destruction of tubulin and actin.…”
Section: The Effect Of Acth 4-10 Synthetic On Separated Junction Formmentioning
confidence: 99%